News, Noise, and the Nature of Politics in Late Medieval English Provincial Towns. (31st March 2017) - Fletcher, Christopher
Abstract: Recent research has stressed the importance of "popular politics" in English political culture especially after the Peasants' Revolt and during the political disturbances of the fifteenth century. Scholars have begun to explore how the structures of local political culture could inflect the nature of politics on a national level, notably through petitioning and the circulation of open letters and manifestos, thus moving beyond the nobility and gentry to consider the influence on late medieval political life of the society and culture of rural and urban communities that were far from the center of power. This article is a contribution to a growing body of work that aims to show how particular aspects of provincial urban politics affected national political culture. By focusing first on news distribution and contemporary conceptual structures that linked rumor, noise, and riot in one continuum; and by then considering the relationship between communal mobilization at times of political crisis and everyday policing institutions such as the hue and cry, the article investigates how the nature of political life in provincial towns affects our understanding of late medieval English political culture as a whole.